Fatwa Lajnah Bahtsul Masail NU Concerning Istibdâl Wakaf and Their Relevance with Renewal of Islamic Law - Nurjanah, Nurjanah; Rahmatsyah, Rahmatsyah; Mutakin, Ali (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This article aims to describe the views and arguments of NU scholars in responding to the concept of istibdâl waqf through the fatwas issued by Lajnah Bahtsul Masail (LBM-NU), and their relevance to Islamic law reform. The concept of istibdâl is basically one way that can be used by policy makers in managing waqf land so that it remains productive. However, the concept of istibdâl has not been fully accepted by scholars. In general, the responses of scholars regarding the concept of istibdâl can be grouped into two. The first group strictly prohibits istibdâl, and the second group allows istibdâl but with strict conditions. The difference is more due to the tendency of the principle that is the weight, namely the principle of eternity (ta’bid al-ashl) and the principle of expediency (tasbîl al-manfa’ah). This research is a normative legal research because it examines the legal provisions, arguments and arguments used. The approach used is a conceptual approach. Primary data sources are fatwa texts issued by NU scholars, while secondary data sources are scientific books, articles, journals, laws related to this research. This study shows that NU scholars allow the practice of istibdâl with agreed terms, namely the existence of disadvantages contained in the waqf object so that the waqf property is in an emergency condition that must be saved. The argument is that the concept of benefit is the spirit of maqâshid syari’ah (the purpose of syari’a), where the value of benefit in istibdâl practice is far greater than its harm. The concept of benefit which is the argument in the fatwa is in accordance with the spirit of reforming Islamic law.